1993
DOI: 10.1210/en.133.5.2379
|View full text |Cite
|
Sign up to set email alerts
|

A primary cell culture system of luteinizing hormone releasing hormone neurons derived from embryonic olfactory placode in the rhesus monkey

Abstract: The purpose of this study is to establish a primary LHRH cell culture system using embryonic olfactory placode and to examine whether LHRH cells derived from olfactory placode and the migratory pathway of LHRH neurons mature in vitro. Six monkey fetuses at the ages of E34-E36 were delivered surgically and the area including the olfactory placode (PL) and the areas that encompass the migratory pathway (MP) were dissected out. The tissues were cut into small pieces and plated on collagen- or poly-L-lysine-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This suggests that the firing patterns and dynamics recorded here from GnRH neurons in vivo are not impacted substantially by pentobarbital anesthesia. Of note, the pentobarbital suppression of pulsatile LH secretion in vivo in rats results from the ensuing hypothermia rather than pentobarbital anesthesia itself (Strutton and Coen, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the firing patterns and dynamics recorded here from GnRH neurons in vivo are not impacted substantially by pentobarbital anesthesia. Of note, the pentobarbital suppression of pulsatile LH secretion in vivo in rats results from the ensuing hypothermia rather than pentobarbital anesthesia itself (Strutton and Coen, 1996).…”
Section: Discussionmentioning
confidence: 99%
“… Uncited references Duittoz et al, 1997; Murase and Horwitz, 2002; Terasawa et al, 1993; Tokuo and Ikebe, 2004. …”
mentioning
confidence: 99%
“…Because transgenic monkeys with GFP-labeled GnRH neurons are not yet available, this approach is quite useful for studying the cellular physiology of GnRH neurons in primates. Earlier, we have demonstrated that 1) cultured GnRH neurons from monkeys contain almost no non-GnRH neurons or glia, as they are not present in the nasal placode at this specific developmental stage (146), 2) cultured GnRH neurons undergo maturational changes in vitro (79,146), and 3) placode derived GnRH neurons are functional, as transplantation of fetal placode into the infundibular recess of the third ventricle of adult female monkeys, in which the GnRH final common pathway has been lesioned, restores cyclic ovulation (125). …”
Section: E2 Induces a Rapid Excitatory Action On Primate Gnrh Neuronsmentioning
confidence: 99%
“…Because our GnRH cultures contain non-neuronal cells (146) and they are involved in the propagation of the [Ca 2+ ] i wave of the GnRH neuronal network (121), it is possible that E 2 action to GnRH neurons are also mediated through non-neuronal cells. In fact, E 2 rapidly induces a [Ca 2+ ] i release from astrocytes, stimulates progesterone synthesis within 5 min in astrocytes of rat hypothalamus which are dependent upon both nonclassical and classical receptors (16,78), and modifies tanycyte morphology (70,113).…”
Section: The Role Of Rapid E2 Action In the Mechanism Of Gnrh Releasementioning
confidence: 99%